KERANGKA PENYELESAIAN SENGKETA BISNIS SYARIAH - Abd Hakim, Atang; al-Hakim, Sofyan (Islamic Economics and Business Faculty of UIN Antasari, 2015)
Abstract: This paper discuss the concept of sharia binsis dispute resolution. In this paper explainedthat the agreement or contract Musharaka mutanaqishah arranged in a deed that fulfill the standard(pillars and conditions shirkah). Thus, tort committed by one of the parties can not be separated fromthe legal reference contained in the KUHPerdata and Kompilasi Hukum Ekonomi Syariah. Applicablelaw in Indonesia has been providing the forum choice: the ways of litigation and non-litigation. Litiga-tion way, sharia business disputes can be solved in Pengadilan Agama atau Pengadilan Negeri (IslamicCourt or the District Court); while the non-litigation way, sharia business disputes can be solved inBasyarnas or BANI through the establishment of a special assembly at the request of the parties to thedispute. All forums examining and adjudicating business disputes sharia required) heed principles shariahcontained fatwa from Dewan Syariah Nasional (National Sharia Council).